Foreign language learning and the European Higher Education Area: impact and implementation after the Bologna Process - Ballesteros Martín, Francisco José (Avances en Supervisión Educativa, 2009)
The European Union authorities have constantly fostered foreign language learning policies due to the special contribution of this competence to social cohesion and economic prosperity. Since Bologna Declaration and the attempt to build a European Higher Education Area, that interest has also extended to decision-making and regulatory bodies in universities. This article reviews the main declarations and implementations to promote multilingual training in universities: The Portfolio in 2001, the Common European Framework of Reference for Languages in 2001, the ENLU network project in 2003 and the Nancy Declaration in 2006. It also describes the situation of Spanish institutions regarding foreign language acquisition. Finally, it provides some suggestions for achieving convergence plans within the EHEA context, expected by the 2010 deadline.